Síntese e caracterização de espinélios de lítio e manganês obtidos via rota hidrotermal assistida por microondas - Silva, Daiane Piva Barbosa da (2014)
Lithium and manganese oxide in spinel phase (LiMn2O4) was obtained by microwave-assisted hydrothermal route starting from completely soluble reagents. For this, a mixture of potassium permanganate and lithium hydroxide monohydrate (Li/Mn = 1.2) aqueous solutions and acetone (acetone/Mn = 1.1) was treated in a microwave reactor (850 W) at 140 °C for different times (10 s - 30 min) and under constant magnetic stirring. The obtained materials were characterized by X-ray diffraction, scanning and transmission electron microscopy, X-ray dispersive energy spectroscopy, electrons diffracton, inductively coupled plasma-atomic emission spectroscopy, cyclic voltammetry, thermogravimetry, structural refinement by Rietveld method and chronopotentiometry. The X-ray diffractogramm for the material synthesized in 5 min could be indexed to the JCPDS card number 35-0782 related to the LiMn2O4 in spinel phase, but the unwanted presence of K+ ions in its structure was verified. Thus, an ionic exchange step was included in the process, in which the newly-synthesized material was treated in an aqueous solution of lithium hydroxide in the same microwave reactor for different times (5 - 40 min) and under constant magnetic stirring. After 10 min, a material with low content of K+ ions and Li/Mn ratio = 0.52 was obtained, but it was electrochemically inactive. The material was submitted to a heat treatments in a conventional microwave oven for distinct times (1 - 5 min), having presented, after 4 min, the characteristic electrochemical profile of the spinel. The images obtained by scanning and transmission electron microscopy for this material showed the predominance of prismatic particles with nearly 10 - 25 nm. The results of charge and discharge tests showed that the specific capacity values are strongly dependent of the composite film thickness that composes the electrode. Thinner films presented a value of initial specific capacity of 100 ± 17 mA h g-1 with charge retention of 93% after 75 charge and discharge cycles at C/1 discharge rate.